1984
DOI: 10.6028/jres.089.024
|View full text |Cite
|
Sign up to set email alerts
|

Indentation Fractography: A Measure of Brittleness

Abstract: Indentation constitutes one of the most powerful test techniques for the systematic investigation of deformation and fracture responses in brittle materials. Indentations can be used to evaluate critical mechanical parameters (toughness, hardness, elastic modulus) with great simplicity and high accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…The force required to remove an atom from the top (111) plane is, therefore, higher. However, a sphere-on-plane contact will generate ring-and/or cone-cracking on Si(111) as well as Si(100) and poly-Si under sufficiently high loads, regardless of the crystal structure [28]. Highfriction tangential sliding under load generates higher tensile stresses in the wake of the tribocontact than those stresses which form the ring and cone cracks under static condition.…”
Section: Predicted Vs Measured Wearmentioning
confidence: 99%
“…The force required to remove an atom from the top (111) plane is, therefore, higher. However, a sphere-on-plane contact will generate ring-and/or cone-cracking on Si(111) as well as Si(100) and poly-Si under sufficiently high loads, regardless of the crystal structure [28]. Highfriction tangential sliding under load generates higher tensile stresses in the wake of the tribocontact than those stresses which form the ring and cone cracks under static condition.…”
Section: Predicted Vs Measured Wearmentioning
confidence: 99%
“…Two types of cracks (e.g., cone, median) of penny shape were observed in indentation of brittle solids during loading, followed by crack closure during unloading. Further, it was found that residual stresses present in the deformed material cause formation of lateral cracks that lead to eventual failure (Lawn, 1993(Lawn, , 1983Lawn and Marshal, 1984).…”
Section: Introductionmentioning
confidence: 98%
“…The brittle-plastic transition defines which failure mechanism is preferred when an initially elastic loading results in failure. Lawn and Marshall (1979) showed that during an indentation test, which is analogous to an asperity collision, the scale of the minimum length crack that experiences brittle rather than plastic failure is c m and it depends on material properties according to…”
Section: Interpretation Of the Minimum Scale Of Grooving As A Sign Ofmentioning
confidence: 99%